2014
DOI: 10.9730/ojccnh.org/v4n2a1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators of Diabetes Self-Management: A Qualitative Study Among Vietnamese Americans

Abstract: This qualitative ethnographic study explored barriers and facilitators of diabetes self-management among Vietnamese Americans (VA). Semi-structured interviews were conducted with a convenience sample of 23 VA with type 2 diabetes ages 43 to 83. The interviews were audio-recorded and transcribed verbatim. NVivo 8 software was used for content analysis. Data revealed participants face many barriers including: low diabetes literacy, limited English proficiency, unhealthy eating habits, lack of time and motivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…A member from the healthcare professional workgroup pointed out that nutrition is often the main focus of self-management among Vietnamese adults with diabetes, and there is relatively little focus on prescribed medication, blood glucose monitoring, risk reduction behaviors, or personal strategies for health promotion, which is consistent with our previous research findings (Nguyen, 2014;Nguyen & Edwards, 2014). CAB members also suggested that the community would benefit from emphasizing the importance of and reason for regularly self-monitoring blood glucose levels, a clear explanation of differences between blood sugars and HbA1c levels, and incorporating family members in this education.…”
Section: Community Input On the Culturally Relevant Dsmes Programsupporting
confidence: 88%
See 1 more Smart Citation
“…A member from the healthcare professional workgroup pointed out that nutrition is often the main focus of self-management among Vietnamese adults with diabetes, and there is relatively little focus on prescribed medication, blood glucose monitoring, risk reduction behaviors, or personal strategies for health promotion, which is consistent with our previous research findings (Nguyen, 2014;Nguyen & Edwards, 2014). CAB members also suggested that the community would benefit from emphasizing the importance of and reason for regularly self-monitoring blood glucose levels, a clear explanation of differences between blood sugars and HbA1c levels, and incorporating family members in this education.…”
Section: Community Input On the Culturally Relevant Dsmes Programsupporting
confidence: 88%
“…All representatives attended the first meeting and the final meeting. The first meeting focused on orienting the CAB members to the study by sharing our previous research findings (Nguyen & Edwards, 2014) and lessons learned regarding health beliefs and diabetes self-management practices among Vietnamese adults (Nguyen & Jones, 2021). Sharing the findings allowed CAB members to have adequate information about the project to permit judgement on the need for community support and participation.…”
Section: Academic-community Team Meetingsmentioning
confidence: 99%
“…In a qualitative study with an ethnographic design by Nguyen and Edwards (), the aim was to examine the barriers and facilitators of diabetes self‐management in a specific population of Vietnamese Americans in Oklahoma. The results revealed that knowledge of both barriers and facilitators of diabetes management can inform health professionals in the care of their clients.…”
Section: Cultural Competence Theoriesmentioning
confidence: 99%
“…Nutrition is often the focus of self-management among US Vietnamese with diabetes, and little focus is placed on medication, blood glucose monitoring, risk reduction behaviors, or personal strategies for health promotion [4][5][6]. Self-management and health behaviors are influenced by cultural beliefs, practices, and availability of resources [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen and Edwards [6] reported that linguistic and cultural differences as well as transportation issues are the main barriers to participating in existing DSMES programs among study participants. Many US Vietnamese living with T2D receive information from family, friends, and others diagnosed with diabetes for knowledge and decision-making around self-care [6]. Without formal DSMES, knowledge gained from informal education may negatively influence self-care behaviors.…”
Section: Introductionmentioning
confidence: 99%